Modelagem e análise numérica da estabilidade lateral com distorção de vigas mistas de aço e concreto - Rossi, Alexandre (2021)
The most rational behavior of steel-concrete composite beams occurs in the case of simply supported elements, in which the concrete is in compression and the steel profile in tension. However, in the continuous and semi-continuous composite beams, in regions close to supports, negative bending moment arise. In this condition, the concrete is in tension, requiring additional reinforcement, and the steel section in compression, being subject to stability phenomena. The most common stability mode in steel-concrete composite beams is Lateral Distortional Buckling (LDB). The current standard procedures verify the LDB starting from the elastic critical moment determination. And, subsequently, they use design curves, such as those derived from the SSRC (Structural Stability Research Council) or ECCS (European Convention for Constructional Steelwork), to determine the LDB strength of steel-concrete composite beams. However, the technical literature shows that the procedures used to determine the LDB elastic critical moment are limited. In addition, it appears that the use of design curves (SSRC and ECCS) proposed for the analysis of stability phenomena in steel elements, are flawed when applied to steel-concrete composite beams. Therefore, in this work, studies about the LDB behavior of steel-concrete composite beams were developed. The investigations were carried out based on the development of a numerical model using the ABAQUS software. With the numerical model properly validated, the following parameters were investigated: I-section, span under negative moment, influence of thickness and slab type, longitudinal reinforcement in the concrete slab, transversal stiffeners in the I-section web and, different distribution of negative moment. With the development of buckling analyses, the LDB elastic critical moment was analyzed, and with the development of post-buckling analyses, the LDB ultimate moment was analyzed. The results showed that the analytical procedures for determining the LDB elastic critical moment, in majority, are conservative. The same behavior was verified in relation to standard and analytical procedures about to the values of the LDB ultimate moment. Finally, with the database obtained in the numerical study, it was proposed, by means of artificial neural networks and multiple regression, analytical procedures to determine the LDB ultimate moment.